Analisis Gambar Siswa Tuna Rungu Ditinjau dari Makna Bahasa Rupa (Bentuk dan Warna) di SLB Dewi Sartika Geluran Sidoarjo - Tri Linggo Wati; Dian Novita (International Consortium of Education and Culture Research Studies, 2018)
Deaf students are students who have deficiencies in the five senses of hearing, but they can still perform drawing and colouring expressions as one way they express their expression. This research was conducted on the students of SLB Dewi Sartika Geluran two students consisting of 1 student of grade 2 and 1 student of class 5, This research will analyze the meaning of visual Language (shape and colour) which is the result of student's work. The method used is qualitative by using qualitative phennomenology, to test the validity of the data then used trianggulasi technique that is in the form of: observation, interview, documentation and then matched with theory, result obtained is: from 2 resource in this research able mengungkaapkan match between drawing with a form that is expressed in the heart by using a written interview and this is the same, as well as between the mood that the source of the feelings through the color expression contained in the interview and documentation of the image, the findings that researchers get is deaf students are easier to express his feelings through pictures rather than through written language, this is apparent when several times they have to express the words of the interview written into the written interview sheet.